Equimosis Periorbitaria No Traumática - Francisco Lopes Morgado; Bárbara Saraiva (Sociedade Galega de Medicina Interna, 2022)
72-year-old man, with no known personal history, admitted for elective surgery. During hospitalization, the patient suddenly develops peri-orbital ecchymosis with associated edema of the tongue and lips, without history of associated trauma. When questioned, the patient reports similar self-limited episodes over the past 2 years. Complementary study was carried out, showing an increased serum immunoglobulin and a monoclonal peak of the gamma fraction in the serum protein electrophoresis. Two cutaneous biopsies of the lesions were performed, revealing deposits of amyloid substance compatible with systemic amyloidosis. During hospitalization, a body CT-scan was also performed, showing osteolytic lesions in both femurs. Considering the high suspicion of associated haematological disease, bone marrow evaluation was performed which was compatible with monoclonal gammopathy of undetermined significance. Amyloidosis is a rare multisystemic disease characterized by the deposition of amyloid in various organs and tissues, and as such, its symptoms can be varied and nonspecific. However, it has some presentations that are more characteristic, such as sudden periorbital bruises ("racoon eyes"). The gradual deposition of amyloid results in progressive damage and loss of organic function and, when left untreated, can cause irreversible damage or even death. Thus, a high degree of suspicion is essential for an early diagnosis to prevent further progression and damage to the organs involved. The appearance of ecchymosis as described should lead the clinician to consider this diagnosis. Amyloidosis can also be associated with other diseases, namely plasma dyscrasias, so, complementary study should be done to identify them.